Extracellular esterase activity as an indicator of endoplasmic reticulum calcium depletion. (17th November 2018) - Trychta, Kathleen A.; Heathward, Emily J.; Sulima, Agnieszka; Bäck, Susanne; Farokhnia, Mehdi; Richie, Christopher T.; Leggio, Lorenzo; Rice, Kenner C.; Harvey, Brandon K.
Abstract: Context: Endoplasmic reticulum (ER) calcium depletion is associated with diverse diseases, including cardiac, hepatic, and neurologic diseases. Objective: The aim of the present study was to identify and characterize an endogenous protein that could be used to monitor ER calcium depletion comparably to a previously described exogenous reporter protein. Materials and methods: The use of a selective esterase-fluorescein diester pair allowed for carboxylesterase activity in extracellular fluid to be measured using a fluorescent readout. Cell culture media from three different cell lines, rat plasma, and human serum all possess quantifiable amounts of esterase activity. Results: Fluorescence produced by the interaction of carboxylesterases with a fluorescein diester substrate tracks with pharmacological and physiological inducers of ER calcium depletion. The fluorescence measured for in vitro and in vivo samples were consistent with ER calcium depletion being the trigger for increased esterase activity. Discussion: Decreased luminal ER calcium causes ER resident esterases to be released from the cell, and, when assessed concurrently with other disease biomarkers, these esterases may provide insight into the role of ER calcium homeostasis in human diseases. Conclusion: Our results indicate that carboxylesterases are putative markers of ER calcium dysfunction.